2018
DOI: 10.15171/bi.2018.34
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: Inhibition of hTERT Gene Expression by Silibinin-Loaded PLGA-PEG-Fe₃O₄ in T47D Breast Cancer Cell Line

Abstract: This paper was published in BioImpacts in 2013 (doi: 10.5681/bi.2013.005).1 Based on an email received from a researcher recently, we were informed that this published paper presented some data (i.e., Fig. 3a and 3b) as same as data presented in three other published papers (i.e., doi: 10.1111/Cbdd.12318; doi: 10.1111/Cbdd.12318; and doi: 10.1186/1477-3155-10-46),2-4 which are considered as the ethical misconduct. This issue was brought up with and comprehensively investigated by the editorial team of BioImpac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Silibinin (SIL), a flavonolignan extracted from Silybum marianum, has been widely investigated for its hepatoprotective, antiinflammatory, antioxidant and anticancer properties (structures shown in ▶Fig. 1a) [10,11]. Furthermore, it has demonstrated considerable efficiency in inhibiting or delaying both tumor initiationand promotion-related incidences in various pre-clinical cancer models such as prostate, colorectal, lung and breast cancer [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Silibinin (SIL), a flavonolignan extracted from Silybum marianum, has been widely investigated for its hepatoprotective, antiinflammatory, antioxidant and anticancer properties (structures shown in ▶Fig. 1a) [10,11]. Furthermore, it has demonstrated considerable efficiency in inhibiting or delaying both tumor initiationand promotion-related incidences in various pre-clinical cancer models such as prostate, colorectal, lung and breast cancer [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic nanoparticles can be used to overcome the issues (Dobson 2006). The magnetic nanoparticles encapsulated with the drug can be arrived to the target position using an external magnetic field and then initiated release of the drug at the proper location (Ebrahimnezhad et al 2013). Therefore, the goal of this study was to synthesize silibinin-loaded PLGA-PEG-Fe 3 O 4 nanoparticles and compared the effects of the pure silibinin and the silibinin-nanomagnetic encapsulated in PLGA-PEG on cell cytotoxicity and hTERT gene expression in A549 lung cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the MTT assay showed that the metabolizing activity of the normal cells was not affected by the PSu; but the drug loaded composites decreased the metabolic activity of the cancerous cells. Thus, the prepared model could potentially be a carrier for anticancer drug, and it could also serve as a postsurgical implant (Ahmadi et al 2014, Ebrahimnezhad et al 2013, Mollazade et al 2013, Pourhassan-Moghaddam et al 2013, Saravanabhavan and Dharmalingam 2013, Zong et al 2015.…”
Section: Nanofiber In Cancer Therapymentioning
confidence: 99%
“…One of the factors causative to poor survival is the lack of ability of a lot of patients to bear a "wide" local cutting out of their tumor, i.e., lobectomy, since elimination of the predictable 25% of whole lung function additional compromises previously restricted pulmonary function. Lesser, i.e., wedge, resections save lung parenchyma but are connected with a two-fold rise in local cancer return as an outcome of the microscopic disease remaining at the surgical resection border (Ebrahimnezhad et al 2013). This is a serious choice since recent two-year survival in patients that grow recurrence drops to 20% (Pourhassan-Moghaddam et al 2013) for instance the mainstream of these patients are not candidates for added surgery, and radiation and/or chemotherapy are largely palliative (Ahmadi et al 2014).…”
Section: Prevention Of Lung Cancer Recurrence By Nanoparticle (Nanofimentioning
confidence: 99%